Renewable Energy From Europe to Africa - Elliott, David (Springer International Publishing, 2018)
Significant progress has been made by industrial countries to reduce emissions from the use of fossil fuels, but as the economies of the less-developed regions of the world begin to expand, they too will face similar challenges. This book looks at energy transitions being made in developing countries, focusing on the adoption of renewable energy systems in Africa, for example under the UN Sustainable Energy for All programme, but also by the EU in the Former Soviet countries of Eastern and Central Europe. It draws on experience from involvement with programmes in the EU and Africa and will be of great interest to academics, policy makers and practitioners in the development aid and renewable energy policy fields.